A new approach to three-phase asynchronous motor model for electric power system analysis - Laura Collazo Solar; Angel A. Costa Montiel; Miriam Vilaragut Llanes; Vladimir Sousa Santos (Institute of Advanced Engineering and Science, 2021)
In this paper, a new steady-state model of a three-phase asynchronous motor is proposed to be used in the studies of electrical power systems. The model allows for obtaining the response of the demand for active and reactive power as a function of voltage and frequency. The contribution of the model is the integration of the characteristics of the mechanical load that can drive motors, either constant or variable load. The model was evaluated on a 2500 kW and 6000 V motor, for the two types of mechanical load, in a wide range of voltage and frequency, as well as four load factors. As a result of the evaluation, it was possible to verify that, for the nominal frequency and voltage variation, the type of load does not influence the behavior of the powers and that the reactive power is very sensitive to the voltage variation. In the nominal voltage and frequency deviation scenario, it was found that the type of load influences the behavior of the active and reactive power, especially in the variable load. The results demonstrate the importance of considering the model proposed in the simulation software of electrical power systems.